Teatro terapia: um estudo com jovens vulneráveis - Rojas, Viviane Ramos (2019)
This study examines how drama therapy can be used to benefit vulnerable adolescents aged twelve to eighteen years with histories of abuse (sexual, verbal and/or physical). The six individuals studied were attending a unit of the Center for Child Psychosocial Care (CAPS-I) in São Paulo, Brazil. The YSR (Youth Self-Report) and BHS (Beck Hopelessness Scale) were employed before and after the interventions to assess the intervention’s impact. The intervention process consisted of nine sessions of drama therapy as practiced by leading drama therapy researchers Phil Jones, Renée Emunah and Robert Landy, with supporting theoretical framework drawn from Carl Gustav Jung’s analytical psychology. Of the several intervention techniques current within drama therapy, the two chosen for this study were narrative with dramatization and theatrical games. The sessions were divided into five stages of intervention, each with a defined purpose, such as self-knowledge, resource expansion, conflict resolution and overcoming traumas. The BHS results improved post-test versus pre-test, while the YSR results displayed significant statistical change in the dimensions depression, anxiety and stress. The drama therapy process was analysed within three categories: “destruction”, “life projects” and “shared empathy”. Discourse involving destruction occurred only at the beginning of the work, showing how this population expresses the hardship of lived vulnerability through suicidal ideation, self-exposure to risk, animal mistreatment and scenes of abuse. The category “shared empathy” progressively developed throughout the whole process, more visibly from the fifth session on, with discourses revealing alterity, compassion, recognition of others’ vulnerability, acceptance and group support. The “life projects” category was expressed along two contradictory dimensions: either viable and hopeful projects or fanciful speculations. The process of drama therapy enabled the dissolution of the rigid persona and created space for other-bonding and shared empathic ties to develop. Drama therapy always takes place dynamically, fluidly and in-the-now, evolving as does a boat in a sea that never bores